2017
DOI: 10.1210/en.2016-1953
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Receptor α Controls Developmental Timing and Regulates the Rate and Coordination of Tissue-Specific Metamorphosis in Xenopus tropicalis

Abstract: Thyroid hormone (T3) receptors (TRs) mediate the effects of T3 on organ metabolism and animal development. There are two TR genes, TRα and TRβ, in all vertebrates. During animal development, TRα expression is activated earlier than zygotic T3 synthesis and secretion into the plasma, implicating a developmental role of TRα both in the presence and absence of T3. Using T3-dependent amphibian metamorphosis as a model, we previously proposed a dual-function model for TRs, in particular TRα, during development. Tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 98 publications
5
86
0
Order By: Relevance
“…If the mutation rate is high, grow up the remaining injected embryos for phenotypic analysis of the Fo knockdown animals, or use the Fo animals to produce total knockout animals for analysis ( see [35, 38]. …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…If the mutation rate is high, grow up the remaining injected embryos for phenotypic analysis of the Fo knockdown animals, or use the Fo animals to produce total knockout animals for analysis ( see [35, 38]. …”
Section: Methodsmentioning
confidence: 99%
“…Such high efficiency suggested that we had nearly a complete knockout of the TRα gene and could study the phenotype in the Fo animals. Indeed, the findings in the Fo knockdown animals were subsequently confirmed by studies on complete TRα knockout animals derived from germ line breeding of the knockdown animals [38, 39]. …”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations